Mergers and Acquisitions in CEE Countries: Example of Poland - Szezepaniak, Angelika Kedzierska (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2009)
The world market economy is currently characterized by the tendency to globalization, which means that companies have to cooperate and tighten their relations. Companies working on the local market do not have many possibilities for development, so mergers and acquisitions (M&A also called consolidations or takeovers) can be a chance for them to cooperate with companies from all over the world. Consolidations (M&A) concern the aspect of management, corporate finance and corporate strategy dealing with buying, selling and merging of different companies. The main goal of mergers and acquisitions is usually an improvement of company performance and shareholder value over a long period of time. Mergers and acquisitions are similar corporate actions - they combine two previously separate companies into a single legal entity. In some cases, terming the combination a "merger" rather than an acquisition is done purely for political or marketing reasons. In a merger of two corporations, the shareholders usually have their shares in the old company exchanged for an equal number of shares in the merged entity.